Authentizität: ein Ereignis der Begegnung - Wiesinger, Christoph (de Gruyter, 2020)
Abstract: With the concept of authenticity, we encounter a phenomenon that is omnipresent in our cultural space. Ever since Heidegger postulated that it corresponds to one’s being to decisively strive towards authenticity, it has become unimaginable to conceive of the disappearance of the latter term from our linguistic world. Yet whom or what do we encounter when we think we have to be true to ourselves? We are cast upon a self which, on closer inspection, turns out to be a complex socially internalized structure. Authenticity is by no means revealed as a congruent figure between representation and being, but as a phenomenon of social attribution. Authenticity does not exist at one’s personal disposal, but rather occurs when another person becomes visible in a positive, unexpected and, as it were, defining way. Authenticity gives cause for reflection on the difference between expectation and experience, for example in inter-religious learning.